Determination of shoulder global range of motion - Gupta Varun (2015)
The objective of this study was to propose a cost effective and user-friendly method of measuring three-dimensional shoulder range of motion for clinical purposes. A motion capture system was utilized to capture the three dimensional data. Six healthy male subjects were asked to pose in seven different postures, as well as perform one motion to measure each of their extreme shoulder range of motion. The positioning of the markers on the subjects, the calculation procedure and the reporting structure for calculated angles was based on the recommendations of the International Society of Biomechanics. Euler angles were used to calculate the orientation of the humerus with respect to the thorax in order to determine the angle for plane of elevation and the angle of elevation. The results of the angles were plotted on a two-dimensional chart. The results indicated that the system used in this study to compute and report the orientation of the shoulder gives more objective, accurate and comprehensive information than current clinical practices. In addition, the angles at each frame of the motion to determine extreme range of motion were plotted as a two-dimensional map. The map serves as a tool to evaluate the complete range of motion of the subject, and any areas of deficiency, thereby potentially aiding in diagnosis and treatment of patients. If future studies collected and reported range of motion data in a standardised manner, as it is in this study, for a large number of healthy individuals, a universal map could be generated of the range of motion expected for a healthy individual. A subject’s shoulder range of motion could then be compared against this map to evaluate it. It could also be compared at various stages of rehabilitation/treatment for a patient, to measure his or her progress. Further research should also be conducted to replace the motion capture technology with simpler, more compact solutions that achieve the same results.